2020
DOI: 10.1176/appi.neuropsych.19030076
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Action Control in Patients With Functional Movement Disorders

Abstract: Objective: Despite being a major cause of neurological disability, the neural mechanisms of functional movement disorders (FMDs) remain poorly understood. Recent studies suggest that FMD is linked to dysfunctional motor and prefrontal regions that could lead to motor and cognitive impairments. The aim of this study was to investigate different components of action control in FMD by using choicereaction, stop-signal, and Simon tasks.Methods: Thirty patients with an FMD were prospectively recruited from the Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…23 R-cluster effects were associated with activation differences in the inferior frontal gyrus, that is, BA44, a hub region of inhibitory control processes to implement executive control, 59,60 which have been shown to be altered in FMD. 61 Our study also shows that translation processes between stimulus processing and responding (C-cluster) are affected in FMD. In fact, C-cluster effects were associated with different activity modulations in the inferior parietal cortex, that is, BA40, an area well known to be relevant for event file coding.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…23 R-cluster effects were associated with activation differences in the inferior frontal gyrus, that is, BA44, a hub region of inhibitory control processes to implement executive control, 59,60 which have been shown to be altered in FMD. 61 Our study also shows that translation processes between stimulus processing and responding (C-cluster) are affected in FMD. In fact, C-cluster effects were associated with different activity modulations in the inferior parietal cortex, that is, BA40, an area well known to be relevant for event file coding.…”
Section: Discussionsupporting
confidence: 62%
“…The latter finding does not contradict the conceptualization of altered perception–action integration in FMD because both sensory and motor processes (R‐cluster) 57,58 constitute processes occurring in an event file 23 . R‐cluster effects were associated with activation differences in the inferior frontal gyrus, that is, BA44, a hub region of inhibitory control processes to implement executive control, 59,60 which have been shown to be altered in FMD 61 …”
Section: Discussionmentioning
confidence: 74%
“…Van Wouwe et al [ 11 ] investigated the ability of FMD patients to control their actions using choice-reaction, stop-signal, and Simon tasks compared to healthy controls. Patients displayed impaired selective impulse inhibition and global action cancellation, suggesting two forms of abnormal inhibitory control in FMD.…”
Section: Updates On Pathophysiologymentioning
confidence: 99%
“…Recent studies have identified various neurophysiological and neuropsychological factors associated with DCD, including the role of executive control dysregulation. 14 15 Researchers have also highlighted possible connections between the amygdala and orbitofrontal cortex (OFC) to process emotional stressors in dissociative symptoms. 16 The connections between OFC and amygdala are necessary for making an effective decision with proper utilization of outcome-related feedback in terms of reward and punishment, as there is a role of these connections in processing emotional and social stimuli.…”
mentioning
confidence: 99%